GENDER IN KAZAKHSTAN’S MINING INDUSTRY - Shtey, Dariya (Nazarbayev University School of Mining and Geosciences, 2022)
Globally, the mining industry has been considered a male-dominated occupation due to various factors. Gender barriers, such as the gender pay gap, "glass ceiling," discrimination, prohibited working positions, and cultural and social stereotypes discourage women from joining or remaining in the mining industry. However, it has been shown that women´s inclusion brings benefits, including a wider talented working pool, support of local expertise, and productive working teams. In addition, with the mining sector's changing economic, social, and operational landscape, there is a strong demand to address gender diversity to attract and retain more females within its workforce. In Kazakhstan´s mineral industry, gender equality reflects the global trend. However, the absence of information in the public domain makes it difficult to accurately assess the depth of the inequity within the mining workforce to-date. This thesis investigated the status of women in the Kazakhstan mining industry by evaluating employment, pay rate, education, and companies’ relation factors. In Kazakhstan’s academia, women's participation is less than male involvement. The results showed that women represent only 15.7 percent of the university cohort studying geology and mining and comprise only 19.2 percent of the mining workforce. Working in the mining industry is highly paid, and the gender gap is decreasing through the years, resulting in 5 percent. Which demonstrates profitable working perspective for all, men, and women. In the employment process, for the past decade, the share of women in the mining sector decreased, which means the promotion of gender diversity by the local companies and existing educational programs do not address the issue. A diverse working force has a broader view with different viewpoints on the development of mining operations. Reconsidering the current state of women in mining labor could lead to socio-economic growth and sustainable development, i.e., preserving local culture strengthening social relations, including ethnic matters. The recognition and understanding of the current gender barriers for women in the mining industry will draw attention to the issues faced by women in mining.
Keywords: Type of access: Open Access; gender studies; mining industry; gender barriers; gender pay gap